Computational systems bioinformatics : CSB2007 Conference proceedings, volume 6, University of California, San Diego, 13-17 August 2007 - Markstein, Peter; Xu, Ying, 1960- (Series on advances in bioinformatics and computational biology., 2007)
This volume contains about 40 papers covering many of the latest developments in the fast-growing field of bioinformatics. The contributions span a wide range of topics, including computational genomics and genetics, protein function and computational proteomics, the transcriptome, structural bioinformatics, microarray data analysis, motif identification, biological pathways and systems, and biomedical applications. Abstracts from the keynote addresses and invited talks are also included. The papers not only cover theoretical aspects of bioinformatics but also delve into the application of n.